2016
DOI: 10.1016/j.cell.2016.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic Insulin Signaling Couples Brain Glucose Uptake with Nutrient Availability

Abstract: We report that astrocytic insulin signaling co-regulates hypothalamic glucose sensing and systemic glucose metabolism. Postnatal ablation of insulin receptors (IRs) in glial fibrillary acidic protein (GFAP)-expressing cells affects hypothalamic astrocyte morphology, mitochondrial function, and circuit connectivity. Accordingly, astrocytic IR ablation reduces glucose-induced activation of hypothalamic pro-opio-melanocortin (POMC) neurons and impairs physiological responses to changes in glucose availability. Hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
426
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 424 publications
(460 citation statements)
references
References 42 publications
(50 reference statements)
27
426
0
7
Order By: Relevance
“…Third, given that LDHA is selectively expressed in the astrocytes (21)(22)(23)(24) and that leptin enhances LDHA-dependent glucose sensing in the hypothalamus as currently described, leptin signaling and glucose-lactate metabolism could intersect within the astrocytes to improve whole-body metabolic control. This postulation is collaborative with findings indicating that leptin signaling in the astrocytes regulates feeding (27) and that insulin signaling in the astrocytes enhances central glucose sensing (28). In summary, we here report, for the first time to our knowledge, that leptin enhances LDHA-dependent hypothalamic glucose sensing to regulate glucose production in high-fat fed in vivo conditions.…”
Section: Discussionsupporting
confidence: 63%
“…Third, given that LDHA is selectively expressed in the astrocytes (21)(22)(23)(24) and that leptin enhances LDHA-dependent glucose sensing in the hypothalamus as currently described, leptin signaling and glucose-lactate metabolism could intersect within the astrocytes to improve whole-body metabolic control. This postulation is collaborative with findings indicating that leptin signaling in the astrocytes regulates feeding (27) and that insulin signaling in the astrocytes enhances central glucose sensing (28). In summary, we here report, for the first time to our knowledge, that leptin enhances LDHA-dependent hypothalamic glucose sensing to regulate glucose production in high-fat fed in vivo conditions.…”
Section: Discussionsupporting
confidence: 63%
“…Interestingly, García-Cáceres et al [34] have recently revisited this concept and showed that intact insulin signaling in astrocytes is required for brain glucose uptake and insulin transport across the blood-brain barrier (BBB). In fact, both astrocytic IR (GFAP-IR) and hypothalamus-specific astrocytic IR (Hyp-GFAP-IR) knockout mice showed a decrease in glucose availability in the CNS, which consequently impaired systemic glucose homeostasis [34]. Noteworthy, this study has provided compelling evidence to prove that glucose transport across the brain is at least in part dependent on astrocytic insulin signaling and nutrient availability.…”
Section: Insulin Action In the Hypothalamusmentioning
confidence: 99%
“…Disruption of insulin signalling in astrocytes afects glucose uptake crossing the blood brain barrier (BBB). It also reduces glucose-induced activation of POMC neurons and impairs hypothalamic mediated suppression of systemic blood glucose [106].…”
Section: Astrocytes In Hypothalamusmentioning
confidence: 99%